2017
DOI: 10.1123/jmld.2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Adults With Down Syndrome Demonstrate Peripheral, Not Central, Deficits When Integrating Movements During Multiple-Target Sequences

Abstract: The perceptual-motor impairments of individuals with Down syndrome (DS) are attributed to central (e.g., neurophysiology deficits that affect the retrieval or initiation of motor programs) and peripheral (e.g., anatomical deficits relating to issues with inertia of limb mechanics and muscle organization) processes. However, recent research suggests that central deficits do not affect the integration between movements. We investigate the impact of central and peripheral DS deficits on movement integration by ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…This increase in RT may not only result when advance information is given on the number of targets but also when the number of targets changes from trial to trial. However, the two segments of an extension task are integrated at the central rather than peripheral level (Reilly, Lawrence, Mottram, & Khan, 2017). This may account for the lack of differences found when comparing the one-to the two-segment task in the alternate condition.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in RT may not only result when advance information is given on the number of targets but also when the number of targets changes from trial to trial. However, the two segments of an extension task are integrated at the central rather than peripheral level (Reilly, Lawrence, Mottram, & Khan, 2017). This may account for the lack of differences found when comparing the one-to the two-segment task in the alternate condition.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that movements in these conditions require the greatest muscular forces (i.e., impulses), the authors contend that those with Down syndrome had difficulties applying the appropriate forces at movement onset (and making adjustments using feedforward control), and that online feedback-based control (i.e., limb-target control) was insufficient to minimize endpoint variability. Results from similar studies showed greater hand-INSIGHTS ON LIMB CONTROL FROM VARIOUS SPECIAL POPULATIONS 11 object contact velocities in children with Down syndrome during a reach-to-grasp task (Valvano et al 2017) and increased movement times for people with Down syndrome in integrated one-arm reversal tasks (Reilly et al 2017), which are indicative of deficits in force specification and insufficient feedback-based online control.…”
Section: Down Syndromementioning
confidence: 93%
“…Previous studies have demonstrated that adults with DS can improve their motor performance during practice (Kerr & Blais, 1985; Reilly et al, 2017), and intervention studies have shown that the group can improve their gross motor skills over several training sessions. The latter has been observed as improvements in gait parameters after 10 weeks of Nordic walking (Skiba et al, 2019) and as improved dribbling skills after 16 weeks of soccer practice (Perić et al, 2021).…”
Section: Introductionmentioning
confidence: 99%